Peasant strategies and diverse use of the territory: consideration of the agroecological experiences in Gravatá, Pernambuco, Brazil - Silva, Izabela Cristina Gomes da; Gonçalves, Claudio Ubiratan (Geosaberes; Vol 9 No 17 (2018): Jan - AprDO - 10.26895/geosaberes.v9i17.605, 2017)
In this article we bring some theoretical reflections and results in the Masters research studies. We have the general objective of analyze the strategies of social subjects peasants to keep in their territories as well as for achieving greater autonomy in the county of Gravatá - PE. We use a qualitative methodology based on an integrative approach of experienced reality. In the 1980s emerged  from discussions related to alternative agriculture and degradation of nature. So in 1997 comes in Gravatá - PE the AMA GRAVATÁ (Association of Friends of the Environment of Gravatá), which disseminates and develops the Agroecology in the peasant territories of Gravatá, Pernambuco, Brazil. Then generating better living conditions for the peasantry.
Keywords: Territórios, Camponeses, Agroecologia